does e^-x*x^(t-1)=(adsbygoogle = window.adsbygoogle || []).push({});

e^(t*ln(x)-ln(x)-x)

heres my reasoning:

x=e^ln(x)

e^-x*x^(t-1)=

e^-x*e^(ln(x)(t-1))=

e^-x*e^(t*ln(x)-ln(x))=

e^(t*ln(x)-ln(x)-x)

I want it in the latter form so that it is easier to take derivatives and antiderivatives. did i make any mistakes?

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Rewriting the function e^-x*x^t-1

**Physics Forums | Science Articles, Homework Help, Discussion**